2018
DOI: 10.14503/thij-16-6178
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Older Donor Age and Cold Ischemic Time on Long-Term Outcomes of Heart Transplantation

Abstract: Using older donor hearts in cardiac transplantation may lead to inferior outcomes: older donors have more comorbidities that reduce graft quality, including coronary artery disease, hypertension, diabetes mellitus, and dyslipidemia. Shorter cold ischemic times might overcome the detrimental effect of older donor age. We examined the relationship between donor allograft age and cold ischemic time on the long-term outcomes of heart transplant recipients. rom 1994 through 2010, surgeons at our hospital performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 19 publications
1
24
0
6
Order By: Relevance
“…With the growing shortage of organ donors combined with the increasing demand for organs, more expanded criteria donors are being used. The use of cardiac allografts from older donors has thus also increased over time, and the percentage of donors above the age of 50 has more than tripled over the past three decades . Earlier ISHLT registry data reported that older donor age was a significant predictor of death at 1 year and 5 years after heart transplantation (HT), but not at 15 years; the correlation between older donor age and higher recipient mortality rates remained significant after multivariate analysis .…”
Section: Introductionmentioning
confidence: 99%
“…With the growing shortage of organ donors combined with the increasing demand for organs, more expanded criteria donors are being used. The use of cardiac allografts from older donors has thus also increased over time, and the percentage of donors above the age of 50 has more than tripled over the past three decades . Earlier ISHLT registry data reported that older donor age was a significant predictor of death at 1 year and 5 years after heart transplantation (HT), but not at 15 years; the correlation between older donor age and higher recipient mortality rates remained significant after multivariate analysis .…”
Section: Introductionmentioning
confidence: 99%
“…Available evidence suggests inferior outcomes for both pediatric and adult recipients of older donor hearts, with a donor age >40 years commonly cited as the cutoff that portends worse survival . Older donor hearts are also more susceptible to ischemic challenges, and therefore, utilization of older donors with anticipated short ischemic times has been suggested as a viable approach to optimize utilization of these organs . Despite this, many pediatric centers reported much lower age cutoffs for adolescent recipients.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, isolated mortalities have a much greater impact 19,21,22 Older donor hearts are also more susceptible to ischemic challenges, 20,23 and therefore, utilization of older donors with anticipated short ischemic times has been suggested as a viable approach to optimize utilization of these organs. 24,25 Despite this, many pediatric centers reported much lower age cutoffs for adolescent recipients. While extension of this age cutoff may be warranted, concerns about the possibility of donor transmitted atherosclerosis and the potential association with allograft vasculopathy 26-28 may continue to dissuade utilization of these organs in pediatric recipients.…”
Section: Criteria Impacting Acceptance Of a Marginal Donormentioning
confidence: 99%
“…The decision to accept donor hearts from remote places with expected long period of ischemia should be a deliberate process based on a detailed assessment of the specific donor and recipient factors . Variables such as recipient comorbidities, particularly donor age, hepatic and renal dysfunction, donor's inotropic use, and left ventricular function should be considered in the decision‐making process . The prolonged cold ischemic time itself should not be the decisive factor for not accepting the donor's heart.…”
Section: Discussionmentioning
confidence: 99%